An agent based simulation of the dynamics in cognitive depressogenic thought - Ab. Aziz, Azizi; Klein, Michel C. A. (2010)
Depression is a common mental disorder. Appropriate support from others can reduce the cognitive distortion that can be caused by subsequent depressions.To increase our understanding of this process, an agent model is presented in this paper in which the positive and negative effects of social support and its relation with cognitive thoughts are modelled. Simulations show the effect of social support on different personality types.A mathematical analysis of the stable situations in the model gives an additional explanation of extreme cases. Finally, a formal verification of expect ed relations between support, risk factors and depressive thoughts is performed on the simulation traces to check whether the simulations describe realistic processes.